Study designs for determining and comparing sensitivities of disease screening tests. (December 2015) - Prorok, Philip C.; Kramer, Barnett S.; Miller, Anthony B.
Objective: To investigate the capability of various study designs to determine the sensitivity of a disease screening test. Methods: Quantities that can be calculated from these designs were derived and examined for their relationship to true sensitivity (the ability to detect unrecognized disease that would surface clinically in the absence of screening) and overdiagnosis. Results: To examine the sensitivity of one test, the single cohort design, in which all participants receive the test, is particularly weak, providing only an upper bound on the true sensitivity, and yields no information about overdiagnosis. A randomized design, with one control arm and participants tested in the other, that includes sufficient post-screening follow-up, allows calculation of bounds on, and an approximation to, true sensitivity and also determination of overdiagnosis. Without follow-up, bounds on the true sensitivity can be calculated. To compare two tests, the single cohort paired design in which all participants receive both tests is precarious. The three arm randomized design with post screening follow-up is preferred, yielding an approximation to the true sensitivity, bounds on the true sensitivity, and the extent of overdiagnosis of each test. Without post screening follow-up, bounds on the true sensitivities can be calculated. When an unscreened control arm is not possible, the two-arm randomized design is recommended. Individual test sensitivities cannot be determined, but with sufficient post-screening follow-up, an order relationship can be established, as can the difference in overdiagnosis between the two tests.